PENINGKATKAN LITERASI DIGITAL SISWA VI MI AL-AMIN CABALU MELALUI SOSIALISASI GADGET DAN MEDIA SOSIAL - Mila Rahmawati; Ahmad Sulkifli; suci rahayu; qudratullah (LPPM Universitas Al-Khairiyah, 2026)
The development of digital technology has had a major impact on children's lives, particularly in terms of their use of gadgets and social media. On the one hand, both can be effective tools for learning and communication, but on the other hand, they also have the potential to cause negative effects if not used wisely. This community service activity aims to provide digital literacy education for sixth-grade students at MI Al Amin Cabalu through a socialization program themed “Wise Use of Gadgets and Social Media.” The activity was carried out using interactive methods that involved material delivery, discussions, ice breaking, and quizzes. The material covered included the definition of gadgets and social media, ideal usage duration, positive and negative impacts, tips for wise usage, and Islamic ethics in digital media. The results of the activity showed an increase in students' understanding of the importance of responsible use of gadgets and social media. Participants also showed high enthusiasm and began to understand the values of balance, trustworthiness, and good intentions in using technology in accordance with Islamic teachings.